Systemic Lupus Erythematosus and DNA Degradation and Elimination Defects - Arneth, Borros (Frontiers in Immunology, 2019)
The pathogenesis of Systemic Lupus Erythematosus (SLE) remains unclear, with numerous studies pointing to a combination of genetic and environmental factors. A critical stage in SLE disease development is cell necrosis, in which undegraded chromatin and nucleoproteins are released into the blood, resulting in circulating cell-free DNA and serum nucleoproteins that trigger anti-dsDNA autoantibody production. The aim of this systematic literature review is to examine whether SLE is a DNA degradation and elimination defect. An advanced literature search was conducted in PubMed. More articles were obtained from the references. A total of 25 peer-reviewed articles published within the past 10 years (2007-2018) were included for review. The findings of each study are summarized. The etiopathogenesis of SLE remains controversial, which limits therapeutic inventions for this disease. However, SLE is a DNA degradation and elimination disorder caused by uncleared histones and nuclear materials that leak to the extracellular space to form cell-free DNA, triggering an immune response that destroys tissues and organs. Normally, apoptosis, DNA and other nuclear materials are efficiently cleared through degradation and other complex mechanisms and thus do not trigger the immune system to produce anti- nuclear autoantibodies.